Direct Optical Patterning of Quantum Dots: One Strategy, Different Chemical Processes - Francesco Antolini (Nanomaterials, 2023)
Patterning, stability, and dispersion of the semiconductor quantum dots (scQDs) are three issues strictly interconnected for successful device manufacturing. Recently, several authors adopted direct optical patterning (DOP) as a step forward in photolithography to position the scQDs in a selected area. However, the chemistry behind the stability, dispersion, and patterning has to be carefully integrated to obtain a functional commercial device. This review describes different chemical strategies suitable to stabilize the scQDs both at a single level and as an ensemble. Special attention is paid to those strategies compatible with direct optical patterning (DOP). With the same purpose, the scQDs’ dispersion in a matrix was described in terms of the scQD surface ligands’ interactions with the matrix itself. The chemical processes behind the DOP are illustrated and discussed for five different approaches, all together considering stability, dispersion, and the patterning itself of the scQDs.